Immune checkpoint inhibitors for patients with preexisting autoimmune neurologic disorders - Fletcher, Kylie; Machaalani, Marc; El Hajj Chehade, Razane; Nassar, Amin H.; Nawfal, Rashad; Manos, Michael; Menzies, Alexander M.; Aboubakar-Nana, Frank; Hassel, Jessica C.; Pinato, David J.; Johnson, Alexandra; Olsson-Brown, Anna C.; et al. (JAMA network open, 2025)
Immune checkpoint inhibitors (ICIs) are efficacious in many cancer types but can produce immune-related adverse events (irAEs). As such, patients with preexisting autoimmune disorders are often excluded from clinical trials, although subsequent studies have shown that many of these patients have acceptable ICI tolerance. The safety and efficacy of ICIs among patients with preexisting neurologic autoimmune disorders (NAIDs) is not well characterized.To evaluate the safety and clinical outcomes associated with ICI therapy among patients with NAIDs.This multicenter retrospective cohort study included patients with cancer who were treated with ICIs between October 2013 and May 2023 and had preexisting multiple sclerosis (MS), myasthenia gravis (MG), Guillain-Barré syndrome (GBS), and other NAIDs as well as a control cohort of patients with Parkinson disease (PD).ICI therapy.Demographic and clinical characteristics (neurologic disability, active or recent immunosuppression), ICI outcomes (response, progression-free survival [PFS], and overall survival [OS]), and safety outcomes (NAID exacerbation, irAEs) were collected.A total of 135 patients were included; the median (range) age was 72 (40-88) years, 84 (62%) were men, and 51 (38%) were women. A total of 45 patients had MS; 18, MG; 10, GBS; 5, another NAID; and 57, PD. Exacerbations occurred most frequently in MG (12 of 18 patients [67%]), often resulting in hospitalization (6 [50%]) or death (2 [17%]), with much lower rates in the MS cohort (8 of 45 patients [18%]). Ten patients with a history of GBS tolerated ICI without exacerbations, although 1 developed a fatal case of Lambert Eaton myasthenic syndrome following ICI treatment. No differences in response rate, PFS, or OS were observed between NAID groups.In this cohort study of ICI use in NAIDs, patients with MG had frequent and more severe exacerbations, while those with MS had few exacerbations. No obvious differences in survival between groups were observed. ICI may be an option for many patients with appropriate oncologic indications and preexisting NAIDs.
Gesehen am 04.11.2025